Contribution of Emanationist Philosophy to the Development of Environmental Conservation - Azizah, Rifqah Najwa; Illahi, Taufik; Sihabussalam, Sihabussalam; Bil Haq, Roshiifah (An-Nida', 2025)
The global ecological crisis demonstrates that contemporary ethical frameworks have been insufficient in mitigating the accelerating rate of environmental degradation. Furthermore, the concept of emanation within Islamic philosophy has not yet been employed as a normative foundation for ecological restoration. This study seeks to examine the potential of the emanation concept in Islamic philosophy as a legitimate ethical framework for environmental conservation. The research adopts a qualitative methodology, utilizing a literature-based approach. The findings indicate that emanation should not be interpreted as a static metaphysical doctrine nor directly employed as a foundation for policy. Instead, it operates as an ontological framework that informs epistemic processes and ethical principles related to the relational nature of existence. This study advances three primary propositions. First, emanation offers an epistemic model that conceptualizes nature as a network of hierarchical interdependencies, thereby suggesting that ecological actions must align with this structure. Second, this epistemic framework engenders an ethical imperative whereby maintaining harmony and sustainability is regarded as a normative obligation. Third, policy instruments—such as tawḥīd-based ecological education, circular economy models, and waste-bank programs—should be understood as practical manifestations of the normative framework derived from emanation, rather than as direct extrapolations of metaphysical doctrine. This study confirms that the concept of emanation provides a pertinent theoretical basis for developing environmental ethics and restoration policies in the framework of contemporary Islamic thought.Abstrak: Krisis ekologi global menunjukkan bahwa kerangka etis modern belum mampu meredam laju kerusakan lingkungan, sementara kajian filsafat Islam khususnya konsep emanasi belum dimanfaatkan sebagai dasar normatif pemulihan ekologis. Studi ini bertujuan menganalisis potensi konsep emanasi dalam filsafat Islam sebagai kerangka etis yang sahih bagi konservasi lingkungan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka. Hasil penelitian menunjukkan bahwa emanasi tidak dapat dipahami sebagai doktrin metafisik statis atau dijadikan dasar kebijakan secara langsung, melainkan sebagai struktur ontologis yang membentuk mekanisme epistemik dan prinsip etis mengenai relasionalitas wujud. Temuan penelitian merumuskan tiga proposisi utama. Pertama, emanasi menyediakan model epistemik yang memposisikan alam sebagai jaringan keberbergantungan hierarkis, sehingga tindakan ekologis harus selaras dengan keteraturan tersebut. Kedua, mekanisme epistemik itu menghasilkan prinsip etis bahwa menjaga harmoni dan keberlanjutan merupakan kewajiban normatif. Ketiga, instrumen kebijakan, seperti pendidikan ekologis berbasis tauhid, ekonomi sirkular, dan bank sampah hanya sah dipandang sebagai ekspresi praksis dari kerangka normatif emanasi, bukan sebagai derivasi langsung dari metafisika. Penelitian ini menegaskan bahwa konsep emanasi menawarkan landasan konseptual yang relevan bagi perumusan etika dan kebijakan pemulihan lingkungan dalam konteks pemikiran Islam kontemporer.